The using of the yeast as a test-object for the guality assessment of the water and liquid environments - K. M. Kazimagomedov; E. Sh. Ismailov (Юг России: экология, развитие)
The considered possibility of the use yeast Saccharomyces cerevisiae as suitable test-object, allowing define the quality of water and her its solution. Certain need of the biological testing in ecological monitoring.